Implementasi Kebijakan Kurikulum Merdeka Pada Sekolah Menengah Atas Negeri di Kabupaten Merauke - Irawan, Andri; Yunitasari, Firda (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
Education is one of the main pillars in the nation's progress, so continuous efforts need to be made to improve the quality of education in Indonesia. Through the Independent Curriculum, schools are free to design learning that suits the needs and context of their region. This research aims to identify and analyze the implementation of the independent curriculum policy in high schools in Merauke Regency. This research uses a qualitative approach where data is obtained through observation and interviews, which are then analyzed by: Data Condensation, Data Display, and Conclusion Drawing/Verifications. The research results show that the implementation of the Merdeka Curriculum in Merauke Regency High Schools still faces various obstacles, especially in the aspects of communication, availability of resources, teacher motivation, and the effectiveness of the bureaucratic structure. Lack of socialization and training causes gaps in understanding between teachers and students, while unequal distribution of resources hinders the learning process, especially in remote areas with limited facilities. Teachers' motivations for implementing this curriculum vary, with adequate support and training playing an important role in successful implementation. In addition, the effectiveness of the bureaucratic structure is not yet uniform in each school, causing differences in program coordination and implementation. Therefore, a more systematic communication strategy is needed, equal distribution of resources, increased training for teachers, and improvements to the bureaucratic structure so that the implementation of the Merdeka Curriculum can run more optimally in Merauke Regency.